Pengaruh Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Camat Merlung - Nurul Anila (Universitas Batanghari Jambi, 2021)
The purpose of this research is to know the of discciplinel condition of work and performance of employees at districk office merlung kab tanjung jabung barat and to know the impact of the working disccipline on the performance of employees at districk office merlung kab.tanjung jabung barat. In discussing this issue authors use quantitative descriptive method that is by looking for information about the symptoms, clearly defined objectives to be achieved, plan the way of approach, collecting data as Materials to create a report. In this research the author held comparisons between discipline condition to the performance of employees in merlung kab . tajung jabung barat. Districk office merlung a government institution is responsible for the provision of services to the community in its working area. The provision of services to distrik office, discipline is one of the main factors for the success of a local government agency. The constant value of 0.840 gives the meaning that if the working disccpline variable (X) is 0, then the performance variable (Y) is worth 0.840. Furthermore, with the simple linear regression equation above, there is a value of variable regression coefficient of work discipline which is positive value of 0,883. If the value of the working environment coefficient is positive if changes to the work environment variables will result in a directional change in the performance variable. In this study, it can be analyzed the magnitude of the working discipline to the performance of 0,883. This means that if the working disicipline of districk office merlung increased by 1%, employees ' performance will increase by 88.3%. Workingt discipline on districk office merlung high employment with an average score of 150,71. Furthermore, employee performance at Districk office Manpower is very high with an average score of 133,4. Based on the hypothesis test it is noted that there is a significant influence between working disicpline and employee performance in districk office . This can is evidenced by the comparison between the calculated T value larger than t table (3,125 > 2,0369). The working discipline can affect performance by 24,6 % and the remaining 76,6% is influenced by other variables not examined in this study